Rupiah Depreciation and Sharia Equity Performance: Evidence from the Indonesian Sharia Stock Index During Economic Turbulence - RIFKI HILMAN FAUZI; Puan Siti Fadillah; Atikah Fadhilah; Fariz Ahmad Zain; Muhammad Almatin Ibnu Sina (SHACRAL: Shari'ah Economics Review Journal, 2026)
This study investigates the impact of the Indonesian Rupiah (IDR) exchange rate against the United States Dollar (USD) on the Indonesian Sharia Stock Index (ISSI) during the 2020–2025 period. Using monthly time-series data comprising 72 observations, the analysis employs the Ordinary Least Squares (OLS) method, supported by the Augmented Dickey–Fuller (ADF) unit root test, classical diagnostic tests, and the Engle–Granger cointegration approach. The ADF results reveal that both variables are non-stationary at level but become stationary after first differencing, indicating integration of order one, I(1). The level regression initially suggests a positive and statistically significant relationship between the exchange rate and ISSI (R² = 0.684). However, the relatively low Durbin–Watson statistic indicates the possibility of spurious regression. After transforming the variables into first differences, the relationship turns negative and remains statistically significant (β = −177.18; p = 0.027), supporting the predictions of the flow-oriented exchange rate model. Furthermore, the cointegration test confirms the existence of a long-run equilibrium relationship between the exchange rate and ISSI. The findings suggest that Rupiah depreciation exerts downward pressure on the Sharia stock market in the short run, while both variables maintain a stable long-run relationship. The contrast between the level and differenced estimations highlights the importance of addressing non-stationarity when examining exchange rate–stock market relationships in Islamic capital markets. This study contributes to the literature by providing updated evidence from a period characterized by the COVID-19 pandemic, post-pandemic recovery, and global monetary tightening, while also emphasizing the methodological importance of distinguishing between short-run dynamics and long-run equilibrium relationships. The findings offer practical implications for investors, regulators, and policymakers in managing exchange-rate-related risks within Indonesia’s Islamic financial market.